The Effect of Corporate Social Responcibility, and Good Corporate Governance on The Financial Performance of The Health Sector Listed on The Indonesia Stock Exchange in 2019-2022 - Widiyantara, I Gede Agus; Pradnyani, Ni Luh Putu Sri Purnama; Wasita, Putu Aristya Adi (International Journal of Pertapsi, 2024)
Financial performance is used as an assumption by investors in seeing the company's success rate. Maximizing financial performance is the same as paying attention to the prosperity of stakeholders. Therefore, companies do not only focus on profits, but need to pay attention to social and environmental conditions. Thus it can attract investors to invest in the company. The purpose of this study was to determine the effect of the implementation of Corporate Social Responsibility, Independent Commissioner, Audit Committee, Constitutional Ownership on the company's financial performance.The research method used is quantitative and qualitative research methods with secondary data. This research was conducted at health sector companies listed on the Indonesia Stock Exchange for the period of 2019 to 2022. The sample determination method used purposive sampling and obtained 52 observation samples. The data analysis technique used is multiple linear regression analysis with data presentation assisted by the SPSS 26 application. The results of this study indicate that the implementation of Corporate Social Responsibility has a positive effect on Financial Performance, Independent Commissioner has a positive effect on Financial Performance, Audit Committee has a positive effect on Financial Performance, while Constitutional Ownership has no effect on Financial Performance. These results are expected to be a consideration for investors in investing, because increasing financial performance is characterized by an increase in the company's share price, so that investors get optimal returns.